In Silico Structure-Activity Study of Selected Triterpenoids as Potential Inhibitors of Mycolic Acid Transporter of Mycobacterial MmpL3 Receptor Protein - Rajab, Mohamed Said (Sciences of Phytochemistry, 2024)
Structural features of the triterpenoid skeleton that are necessary for antimycobacterial activity are not well understood. Following the isolation of the triterpenoids ergosterol-5,8-endoperoxide, 6β-hydroxykulactone, 12β-hydroxykulactone, (24R)-24,25-epoxycycloartan-3-one and (3β,24R)-24,25-epoxycycloartan-3-ol, and (3β,24R)-24,25-epoxycycloartan-3-acetate with varying antimycobacterial activity ranging between MIC of 1 µg/ml to128 µg/ml prompted us to study this class of compounds further to shade light on the structural features necessary for their antimycobacterial activity. This in silico study involved docking the triterpenoids on the mycobacterial multi-pharmacophore receptor protein MmpL3. The docking results were compared with the MmpL3 receptor protein co-crystallized TB drug candidate, AU1235, (1-(2-adamantyl)-3-[2,3,4-tris(fluoranyl)phenyl] urea). The virtual screening revealed key structural features in the triterpenoid skeleton, including the C-3 keto and β-hydroxy group on C-3 or C-6, as important for antimycobacterial activity. Also, the decreased binding affinity for compounds 2 and 7 with an acetate group on C-3 were in tandem with those observed in vitro. Toxicity predictions revealed that this class of compounds had no mutagenic effects and displayed favorable pharmacokinetic parameters. The study reveals the potential of the triterpenoid skeleton exemplified by the readily available ergosterol-5,8-endoperoxide as a useful scaffold in searching and developing effective therapeutic lead entities to facilitate anti-tuberculosis drug discovery.